2020
DOI: 10.1111/evo.14094
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete convergence of gliding mammal skeletons*

Abstract: Ecology and biomechanics play central roles in the generation of phenotypic diversity. When unrelated taxa invade a similar ecological niche, biomechanical demands can drive convergent morphological transformations. Thus, examining convergence helps to elucidate the key catalysts of phenotypic change. Gliding mammals are often presented as a classic case of convergent evolution because they independently evolved in numerous clades, each possessing patagia ("wing" membranes) that generate lift during gliding. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 98 publications
(266 reference statements)
7
69
0
Order By: Relevance
“…These results indicate the similarity of these morphological traits in the terrestrial and arboreal locomotory modes in Euarchontoglires. Interestingly, we found that the gliding species from Rodentia (RG group) were located between the arboreal species (RA, PA, and SA groups) and the gliding species from Dermoptera (DG group), consistent with the observation that the RG group species have evolved their morphological characteristics by not only adapting to tree-dwelling and branch-grasping life, but also to the gliding movement (Samuels and Van Valkenburgh, 2008;Grossnickle et al, 2020). The gliding species from Dermoptera are most distantly separated from the other species.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…These results indicate the similarity of these morphological traits in the terrestrial and arboreal locomotory modes in Euarchontoglires. Interestingly, we found that the gliding species from Rodentia (RG group) were located between the arboreal species (RA, PA, and SA groups) and the gliding species from Dermoptera (DG group), consistent with the observation that the RG group species have evolved their morphological characteristics by not only adapting to tree-dwelling and branch-grasping life, but also to the gliding movement (Samuels and Van Valkenburgh, 2008;Grossnickle et al, 2020). The gliding species from Dermoptera are most distantly separated from the other species.…”
Section: Resultssupporting
confidence: 85%
“…A great diversity in locomotory modes is observed among and within the Euarchontoglire orders, including fossorial, ricochetal, arboreal, terrestrial, and gliding (Macphee, 1993). Interestingly, the same locomotory modes are found in different orders of Euarchontoglire, including the arboreal mode in Scandentia, Rodentia, and Primates, the terrestrial mode in Scandentia and Rodentia, and the gliding mode in Dermoptera and Rodentia (Kirk et al, 2008;Meng et al, 2017;Vander Linden et al, 2019;Grossnickle et al, 2020; Figure 1). The sharing of locomotory modes among orders makes Euarchontoglires an intriguing group for the investigation of morphological convergence with locomotory modes.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations